2020
DOI: 10.1016/j.watres.2019.115382
|View full text |Cite
|
Sign up to set email alerts
|

Improving wastewater management using free nitrous acid (FNA)

Abstract: 4.4 The FNA-based applications are feasible and economically viable in wastewater treatment systems .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(53 citation statements)
references
References 191 publications
1
51
0
1
Order By: Relevance
“…A previous study found that after activated sludge was treated with 1.2 mg/l FNA for 18 h, the activity of NOB could be completely inhibited, while the activity of AOB remained above 57% ( Jiang et al, 2018 , 2019 ). Other researchers have reported similar results, but with differences in FNA concentrations and treatment times due to diversity in sludge properties and microbial community structure and composition ( Duan et al, 2020 ). For example, Wang et al (2014) reported that AOB activity could still be maintained at approximately 50% after activated sludge was treated with 1.35 mg/l of FNA for 24 h, while NOB completely lost its activity, while treatment conditions that can completely inactivate NOB while retaining 47% of AOB’s activity are: A FNA concentration of 0.25 mg/l and a treatment time of 18 h was proposed ( Wang et al, 2019 ).…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…A previous study found that after activated sludge was treated with 1.2 mg/l FNA for 18 h, the activity of NOB could be completely inhibited, while the activity of AOB remained above 57% ( Jiang et al, 2018 , 2019 ). Other researchers have reported similar results, but with differences in FNA concentrations and treatment times due to diversity in sludge properties and microbial community structure and composition ( Duan et al, 2020 ). For example, Wang et al (2014) reported that AOB activity could still be maintained at approximately 50% after activated sludge was treated with 1.35 mg/l of FNA for 24 h, while NOB completely lost its activity, while treatment conditions that can completely inactivate NOB while retaining 47% of AOB’s activity are: A FNA concentration of 0.25 mg/l and a treatment time of 18 h was proposed ( Wang et al, 2019 ).…”
Section: Introductionsupporting
confidence: 56%
“…Under such process conditions, an insufficient carbon source in the influent will lead to insufficient denitrification, resulting in an excessively high concentration of total nitrogen (nitrate nitrogen) in the effluent ( Rahimi et al, 2020 ). In order to solve the problems of high energy consumption, carbon source shortage, and low nitrogen removal efficiency faced by traditional nitrogen removal processes, novel processes based on partial nitritation have gradually developed in recent years, such as the partial nitritation and denitrification process (PN/D) and the partial nitritation and anaerobic ammonia oxidation process (PN/A; Duan et al, 2020 ; Li et al, 2020 , 2021 ; Qiu et al, 2020 ; Yao et al, 2021 ). Different from the traditional nitrification and denitrification process, nitrogen removal processes based on partial nitritation only oxidizes ammonia to nitrite, and then directly enters the subsequent nitrogen removal stage, which greatly saves oxygen consumption and carbon source demand, while reducing excess sludge production and greenhouse gas emissions ( Sinha and Annachhatre, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mechanism of FNA inhibition, NO 2 À acts as a decoupling agent to diffuse into the membrane of prokaryotic cells; the permeability expansion of the cell membrane affects the enzymes involved in electron transport and proton transfer, thereby affecting the inhibition of the synthesis of adenosine triphosphate (ATP). 55,56 Finally, it will affect the ATPasecatalyzed reaction and reduce biological activity. Studies have shown that in order to ensure safe and stable operation of the reactor, the IC 10 value can usually be used as a safe value, 54,57,58 and the FNA concentration should be controlled between 1.5 and 5 mg L À1 .…”
Section: Engineering Applicationmentioning
confidence: 99%
“…In the mechanism of FNA inhibition, NO 2 − serves as an uncoupling agent to pass through the membrane of prokaryotic cells; the permeability expansion of the cell membrane influences the enzymes involved in the transfer of electrons and protons, thereby causing the inhibition of adenosine triphosphate (ATP) synthesis. Ultimately, the ATPase-catalyzed reaction will be affected and the biological activity will be reduced (Duan et al 2019;He et al 2018). Therefore, pH could impact the process not only directly, but also indirectly through its relationship with FA and FNA.…”
Section: Effect On Phmentioning
confidence: 99%